WORKERS’ EDUCATION: A TOOL FOR WORKERS’ EMPOWERMENT IN NIGERIA - Murtala Akanbi, Yusuf; Zakari, Bala (European Scientific Journal, ESJ, 2013)
﻿Workforce remains indispensable machinery through which goods and services are produced. Therefore, no society could succeed without having working class whose efforts are geared towards attaining societal development. The employment patterns and trends as well as technological changes of our society have called for continuous learning opportunities of workers to be able to fit in to the scheme of work dynamic situations and conditions. The welfare of workers and their family members is very important, in fact exploitation of workers of any form must be fought to enable workers gain their personality as individuals and members of the society. The position of this paper is that workers’ welfare, whether at work or home will be greater improved when they are better educated, an illiterate worker not only faces a risk of work-loss but a very limited opportunity for re-engagement as well. He or she also receives better remuneration and self-fulfilled as well as attaining professional happiness. It is against this background that this paper advocates for workers’ education as a tool for workers’ empowerment through its specially designed programs; Literacy education, Vocational skills, labor education, pre-retirement education, leisure education, development education and computer education.